Examining Service Quality at the Destination Level: The Case of Malaysia - Ghani, Nur Izzati Ab; Nasir, Muhamad Nasyat Muhamad; Afthanorhan, Asyraf; Mohamad, Mahadzirah; Rasdi, Aikal Liyani Mohd; Khan, Nur Farihin Abd Hadi; Arshad, Pg Mohd Auza’e Pg (Journal of Tourism Management Research, 2022)
Studies on service quality have gained significant attention from practitioners, managers, and researchers in the tourism industry. Malaysia is experiencing an unstable and declining pattern in the rate of international tourists’ expenditure on services they receive in this country, highlighting a severe challenge in planning the right services to offer tourists since they refuse to spend on the services provided. Therefore, this research investigated the dimensions of service quality at the destination level to improve the quality of a destination. Self-administered questionnaires were distributed to international tourists from the United Kingdom and Australia at Kuala Lumpur International Airport. The pilot study’s data, involving 100 respondents, were tested using Exploratory Factor Analysis (EFA) and reliability analysis. Subsequently, 337 usable questionnaires were collected from fieldwork and analyzed using Confirmatory Factor Analysis (CFA). The study findings identified four dimensions of destination service quality: health and hygiene, accommodation, shopping, and information facilities. In addition, it suggested that tourism management and local citizens (Malaysians) should focus on these four dimensions to enhance the overall quality of service in Malaysia, thereby enhancing tourist satisfaction and spending on the services provided in the country. The limitation of this research was that the data were collected solely at Kuala Lumpur International Airport (KLIA). Future research may include other Malaysian international airports to strengthen the generalizability of the results.